Data and analytics in corporate real estate: The importance of talent - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2015)
Data and analytics are set to play a more pivotal role incorporate real estate (CRE) over the next three years.As organizations recognize that data-driven insights candramatically improve decision making across a broadrange of business functions, they are seeking to capitalizeon and incorporate data and analytics in their CREprocesses.